The Absolute Competence of the Industrial Relations Court in Resolving Employment Termination Disputes - Ndun, Ivan; Helan, Yohanes G. Tuba; Pekuwali, Umbu Lily (Universitas Negeri Semarang, 2020)
Employment relations are subject to contracts agreed upon by employers and employees. Law Number 13 of 2003 clearly defined that employment relations as an agreement between an employer and their employees. The jurisdictional scope or competence of the Industrial Relations Court is further elaborated in Section 56 Law Number 2 of 2004. However, Section 56 Number Law 2 of 2004 has spurred further debate regarding the proper competence of the Industrial Relations Court, because, under this law, the Court has issued ineffective and inefficient court decisions. This research analyzed and criticized the competence of the Industrial Relations Court in presiding over the termination of employment contracts. In analyzing this problem, this paper deploys the theory of competence, theories of justice and the rule of law, subjective justice, the competence of the Industrial Relations Court according to existing laws, and expert views on the contribution of existing literature towards the competence of the Industrial Relations Court. This research emphasized that an excess of laws governs the termination of employment contracts, which supposedly lies under the competence of the Industrial Relations Court. Hence, to protect the rights of employees in the context of industrial relations, a judicial review of Law Number 2 of 2004 on Manpower is required.